Immediate Effects of Dasatinib on the Migration and Redistribution of Naïve and Memory Lymphocytes Associated With Lymphocytosis in Chronic Myeloid Leukemia Patients - Colom-Fernández, Beatriz; Kreutzman, Anna; Marcos-Jiménez, Ana; García-Gutiérrez, Valentín; Cuesta-Mateos, Carlos; Portero-Sainz, Itxaso; Pérez-García, Yaiza; Casado, Luis Felipe; Sánchez-Guijo, Fermín; Martínez-López, Joaquín; Ayala, Rosa M.; Boqué, Concha; et al. (Frontiers in Pharmacology, 2019)
Introduction: Dasatinib is a dual SRC/ABL tyrosine kinase inhibitor used to treat chronic myeloid leukemia (CML) that is known to have unique immunomodulatory effects. In particular, dasatinib intake typically causes lymphocytosis, which has been linked to better clinical response. Since the underlying mechanisms are unknown and SRC family kinases are involved in many cell motility processes, we hypothesized that the movement and migration of lymphocytes is modulated by dasatinib. Patients, Materials and Methods: Peripheral blood samples from CML patients treated with second-line dasatinib were collected before and 2 h after the first dasatinib intake, and follow-up samples from the same patients 3 and 6 months after the start of therapy. The migratory capacity and phenotype of lymphocytes and differential blood counts before and after drug intake were compared for all study time-points. Results: We report here for the first time that dasatinib intake is associated with inhibition of peripheral blood T-cell migration toward the homeostatic chemokines CCL19 and CCL21, which control the trafficking toward secondary lymphoid organs, mainly the lymph nodes. Accordingly, the proportion of lymphocytes in blood expressing CCR7, the chemokine receptor for both CCL19 and CCL21, decreased after the intake including both naïve CD45RA+ and central memory CD45RO+ T-cells. Similarly, naïve B-cells diminished with dasatinib. Finally, such changes in the migratory patterns did not occur in those patients whose lymphocyte counts remained unchanged after taking the drug. Discussion: We, therefore, conclude that lymphocytosis induced by dasatinib reflects a pronounced redistribution of naïve and memory populations of all lymphocyte subsets including CD4+ and CD8+ T-cells and B-cells.